Pengaruh Umur Listing dan Ukuran Perusahaan terhadap Ketepatan Waktu Corporate Internet Reporting (CSR) pada PT Bank Panin Dubai Syariah Tbk Tahun 2019-2022 - Rahayu, Risti Putri; Tripalupi, Ramadhani Irma; Muslih, Amar (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
The purpose of this research is to find out and analyze 1) the influence of listing age on Corporate Internet Reporting (CIR) timeliness 2) company size influence on Corporate Internet Reporting (CIR) timeliness 3) listing age and company size influence accuracy Corporate Internet Reporting (CIR) time at PT. Bank Panin Dubai Syariah Tbk in 2019-2022. The research method in this thesis uses a descriptive method with a quantitative approach. Statistical test tools used include multiple linear regression analysis, analysis of the coefficient of determination, and hypothesis testing using t-test and f-test analysis. the processed data is quarterly financial report data, annual financial reports, and annual reports of PT. Bank Panin Dubai Syariah Tbk in 2019-2022. The results of this study state that: 1) The age of the listing has an R Square value of 0.089, this indicates that 0.089 or 8.9% of corporate internet reporting timeliness can be described by the listing age variable, 2) Company size has an R Squere value of 0.227 , this shows that 0.227 or 22.7% timeliness of corporate internet reporting can be described by company size variables, 3) Listing age and company size have an R Squere value of 0.333, this shows that 0.333 or 33.3% timeliness corporate internet reporting can be explained by the variable age of listing and company size.